2015
DOI: 10.2340/00015555-1959
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Itch: An Expert Position Statement from the Special Interest Group (SIG) of the International Forum on the Study of Itch (IFSI)

Abstract: In clinical practice, the term "paraneoplastic itch" is used to describe itch in patients with cancer. Patients with hematological or solid tumor malignancies can be affected. In general, paraneoplastic itch is considered a rare disorder. However, paraneoplastic itch in hematological malignancies such as polycythemia vera and lymphoma are relatively frequent while other forms of paraneoplastic itch are in fact extremely rare. The true frequency of this symptom is unclear, epidemiological data in this field are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 51 publications
0
32
0
6
Order By: Relevance
“…This agent was found to be efficacious in a crossover, double-blind, randomized, controlled trial [155]. It has also been mentioned as a potential treatment for paraneoplastic itch [89].…”
Section: Systemic Treatmentsmentioning
confidence: 97%
See 2 more Smart Citations
“…This agent was found to be efficacious in a crossover, double-blind, randomized, controlled trial [155]. It has also been mentioned as a potential treatment for paraneoplastic itch [89].…”
Section: Systemic Treatmentsmentioning
confidence: 97%
“…Itch related to cancer is known as paraneoplastic itch and was recently defined as ''the sensation of itch as a systemic reaction to the presence of a tumor or a hematological malignancy neither induced by the local presence of cancer cells nor by tumor therapy. It usually disappears with remission of the tumor and can return with its relapse'' [89]. Multiple case reports and some clinical studies have reported generalized itch as an important skin symptom in cancer patients [78,90].…”
Section: Systemic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wenn eine direkte neoplastische Invasion oder Kompression durch einen Tumor die Ursache für Juckreiz ist, gilt dies nicht als paraneoplastischer Pruritus. 2015 definierte die Special Interest Group des «International Forum on the Study of Itch» den paraneoplastischen Pruritus wie folgt: ‹Juckreiz als systemische (nicht lokale) Reaktion auf das Vorliegen eines Tumors oder einer malignen hämatologischen Erkrankung, der weder durch lokal vorhandene Tumorzellen noch durch die Tumortherapie hervorgerufen wird› [2]. …”
Section: Definition Und Klinische Merkmaleunclassified
“…27,33 The symptom precedes the diagnosis or occurs early in the clinical course of the malignancy. Patients may present with secondary skin findings as a result of scratching, including excoriations, hyper-and hypopigmented lesions, lichenification, prurigo nodules, and scars.…”
Section: Dermatologic Syndromesmentioning
confidence: 99%